Performance Analysis of Corrugated Steel Plate Shear Wall with Geometry Variations - Annasia Faza Nadiva; Budi Suswanto; Aniendhita Rizki Amalia (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2025)
The use of stiffening elements in steel plate shear wall (SPSW) systems enhances lateral stiffness and energy dissipation capacity; however, it also significantly increases material and labor costs due to the complexity of fabrication and installation. As an alternative, the Corrugated Steel Plate Shear Wall (CoSPSW) system has been proposed as a more efficient and practical solution that maintains sufficient stiffness and strength without requiring additional stiffeners. This study investigates the structural performance of CoSPSWs with varying corrugation geometries using the finite element method. The analysis focuses on the influence of the corrugation angle on the overall structural behavior, including buckling stability, lateral stiffness, ultimate strength, and energy dissipation capacity. Nonlinear finite element simulations were conducted using ABAQUS software to capture the influence of geometric nonlinearities under lateral cyclic loading. The results show that increasing the corrugation angle significantly improves lateral stiffness and energy dissipation capacity, while maintaining stable post-buckling behavior. An optimal corrugation angle of approximately 60° provides the maximum strength and ductility among the specimens. This study contributes to understanding the behavior of corrugated steel shear walls and provides valuable insights for the design of efficient, cost-effective steel structures.